Effervescence and Solidarity in Religious Organizations. Issue 2 (June 2014) - Draper, Scott
<x xml:space="preserve">Abstract</x> In the ritual theories of Durkheim and Collins, collective effervescence is the engine that drives social solidarity. I use data from religious organizations to perform a rare test of this hypothesis. In addition, four other hypotheses from Collins's interaction ritual theory are tested regarding ritual dynamics that are expected to promote effervescence and solidarity. Congregational data from the 2001 United States Congregational Life Survey reveal the following: (1) organizational attendance rates strongly correlate with the dependent variables; (2) longer rituals tend to be more emotionally rewarding, although there appear to be diminishing returns for symbolic solidarity; (3) crowded rituals are more rewarding, although socioeconomic status is a crucial intervening variable; (4) barriers to outsiders in the form of behavioral proscriptions correlate with symbolic solidarity; and (5) most important, there is a consistent and robust relationship between effervescence and solidarity. Interaction ritual theory provides a valuable framework for understanding how some religious organizations become more effective than others at providing emotional and symbolic rewards for their members.